2014
DOI: 10.1038/ki.2013.342
|View full text |Cite
|
Sign up to set email alerts
|

Lipopolysaccharide-induced cross-tolerance against renal ischemia–reperfusion injury is mediated by hypoxia-inducible factor-2α-regulated nitric oxide production

Abstract: Although the protective effect of lipopolysaccharide (LPS) pretreatment on renal ischemia/reperfusion injury is known, a link to hypoxia-inducible factors (HIFs) has not been established. Here we show that LPS treatment led to HIF-2α accumulation in mouse kidneys and endothelial cells, a result of nuclear factor-κB activation. Inactivation of HIF-2α, rather than HIF-1α, completely negated LPS-mediated protection against renal ischemia/reperfusion injury. LPS-stimulated renoprotection was related to inducible/e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 57 publications
(59 citation statements)
references
References 74 publications
0
58
0
1
Order By: Relevance
“…In this context, increased VE-PTP expression mediated by HIF2α promotes VE-cadherin interactions at AJs and thus strengthens the endothelial barrier. We observed that HIF2α-mediated VE-PTP expression was physiologically relevant and represented a fundamental adaptive response to tissue hypoxia and inflammation, both of which are characterized by stabilization and nuclear translocation of HIF2α (32). The importance of this mechanism was evident by the finding that EC-specific deletion of Hif2a (Hif2a EC-/-) in mice enhanced endothelial permeability as well as leukocyte extravasation in lungs secondary to inhibition of VE-PTP expression.…”
Section: Discussionmentioning
confidence: 61%
See 1 more Smart Citation
“…In this context, increased VE-PTP expression mediated by HIF2α promotes VE-cadherin interactions at AJs and thus strengthens the endothelial barrier. We observed that HIF2α-mediated VE-PTP expression was physiologically relevant and represented a fundamental adaptive response to tissue hypoxia and inflammation, both of which are characterized by stabilization and nuclear translocation of HIF2α (32). The importance of this mechanism was evident by the finding that EC-specific deletion of Hif2a (Hif2a EC-/-) in mice enhanced endothelial permeability as well as leukocyte extravasation in lungs secondary to inhibition of VE-PTP expression.…”
Section: Discussionmentioning
confidence: 61%
“…The contextual aspect of VE-PTP's role in stabilizing the endothelial barrier also needs to be considered in light of a recent study, which showed that inhibiting VE-PTP by a smallmolecule inhibitor stabilized the ocular vasculature in experimental models of retinal neovascularization (30). In that study, the barrier-stabilizing effects of VE-PTP inhibition were attributed to suppression of VEGF-induced permeability as well as increased TIE2 activation, because TIE2 is a binding partner of VE-PTP (32). Our observation that VE-PTP activation stabilizes the endothelial barrier may be explained by differences in TIE2 and VEGF signaling in the ocular vasculature undergoing angiogenesis and by the lung endothelium responding to acute endotoxin-mediated injury.…”
Section: Methodsmentioning
confidence: 99%
“…19 In this study, a combination of LPS/CGS21680 reduced the renal injury to a surprising extent in WT mice, but had no effect in Mx1-HIF-2a …”
Section: Cgs21680/lps Produced Amentioning
confidence: 99%
“…19 Lck-Cre (stock number: 003802), Mx1-Cre (003556) transgene mice, HIF-2a floxed mice (008407), as well as Rag1KO mice (002216) were all from The Jackson Laboratory (Bar Harbor, ME). The mating strategy, genotyping and the confirmation of target gene excision are described in the Supplemental Material.…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation